Tumor-Infiltrating Lymphocytes: Clinical Experience. Issue 6 (November 2015) - Besser, Michal J.; Shapira-Frommer, Ronnie; Schachter, Jacob
Abstract : Abstract: Adoptive cell therapy (ACT) with tumor-infiltrating lymphocytes (TILs) in combination with lymphodepletion and high-dose interleukin 2 has shown reproducible objective response rates of approximately 50% in patients with highly advanced, refractory metastatic melanoma. As confirmed by different clinical centers, TIL ACT can yield durable responses especially in patients with complete regression, who are mostly disease-free many years after treatment, suggesting the possibility of cure. Most TIL ACT trials have been conducted as salvage therapy for patients with multiple metastases, frequently in visceral organs and even brain, and who failed numerous treatments, including checkpoint inhibitors, which underlines the value of the treatment. Recent developments in the identification and selection of tumor-specific T-cell populations have facilitated the implementation of TIL ACT also in nonmelanoma malignancies. We summarize the clinical experience of TIL ACT in melanoma, briefly discuss new directions for further improvement of this promising therapy, and present the latest clinical results in nonmelanoma cancers.